Note from the editor: Crisis of capitalism? Economic crisis? Crisis of economic sociology? - Mariana Heredia (economic sociology. perspectives and conversations, 2024)
What new can be said about crisis? What can be added that does not resonate, at least in most of the West, to a litany that has been documenting and warning, for almost five decades, about the worsening social inequalities and the monetary and financial collapses that are multiplying and spreading? It is not that there has been a lack of analysis of the crises so far. Alongside a literature attentive to environmental degradation and the difficulties of advancing prudential agreements and legislation, the events of 2008-2009 attracted particular attention from the social sciences and most particularly from economic sociology.
Keywords: 300